Effects of subsidy on publication outputs: Can small research grants lead to higher quality scientific articles? - Valeria Nemethova; Miroslav Šipikal; Alexandra Salamonova (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2022)
Universities play a crucial role in new knowledge production that is considered as key driver of economic growth. Hence, the support of university research is essential, usually provided by the public sector. This article presents an evaluation of small grants of universities through examining research projects in the field of economics implemented in years 2008-2018 in Slovakia. A negative binomial regression analysis was used to determine the effects of small grants on publication outputs of supported researchers. Impact of subsidy on the number of all publications and separately on the quantity of higher quality scientific articles was distinguished. Results show a slight positive impact of the volume of funds on overall publication outputs, even though other factors seem to be more important as the size of the research team, the proximity to the capital city as well as the quality of faculty at which the project is implemented. Conversely, the impact of the volume of funds on higher quality publication appears to be not significant. In this case, more substantial are factors indicating the previous reputation of the research team, ranking of faculty and general research environment. Our findings indicate that researchers with great publication activity are willing to report high quality scientific articles in forthcoming periods regardless the support. Ergo, less active scientists are not benefiting from small grant in terms of their publication improvement.
Keywords: H52; I28; G28; 330; project funding; small grants; economic research; universities; negative binomial regression